Japanese Tales of Lafcadio Hearn - Hearn, Lafcadio, 1850-1904 (Book collections on Project MUSE., 2019)
A collection of twenty-eight stories inspired by Japanese folk tales and written by Western expatriate Lafcadio Hearn. Born in Greece and raised in Ireland, Hearn was a true prodigy - and world traveler. He worked as a reporter in Cincinnati, New Orleans, and the West Indies before heading to Japan in 1890 on a commission from Harper's. There, he married a Japanese woman from a samurai family, changed his name to Koizumi Yakumo, and became a Japanese subject. An avid collector of traditional Japanese tales, legends, and myths, Hearn taught literature and wrote his own tales for both Japanese and Western audiences. Hearn's tales span a variety of genres. Many are ghost stories, such as "The Corpse-Rider," in which a man foils the attempts of his former wife's ghost to haunt him. Some are love stories in which the beloved is not what she appears to be: in "The Story of Aoyagi," a young samurai narrowly escapes the wrath of his lord for marrying without permission, only to discover that his wife is the spirit of a willow tree. Throughout this collection, the author's reverence for Japan shines through, and his stories provide insights into the country's artistic and cultural heritage. With an introduction by Andrei Codrescu discussing the author's life and work, as well as a foreword by Jack Zipes, this text provides a unique window into one writer's multicultural literary journey